Primary ciliary dyskinesia in Israel: Prevalence, clinical features, current diagnosis and management practices. (October 2016) - Abitbul, Revital; Amirav, Israel; Blau, Hannah; Alkrinawi, Soliman; Aviram, Micha; Shoseyov, David; Bentur, Lea; Avital, Avraham; Springer, Chaim; Lavie, Moran; Prais, Dario; Dabbah, Husein; et al.
Abstract: Background: Primary Ciliary Dyskinesia (PCD) is rare and its features in Israel have not been described. Aims: to assess prevalence utilizing state-of-the-art diagnostic techniques, and describe clinical features, diagnostic and management practices in Israel. Methods: A national multicenter study from 2012 to 2013 recruited patients diagnosed or suspected of having PCD. Diagnosis was verified using: nasal Nitric Oxide (nNO); High-speed Video Microscope Analysis (HVMA); Transmission Electron Microscopy (TEM) of cilia; Immuno-fluorescence staining (IF) for ciliary proteins, and genetic analysis. Results: Of the 203 patients recruited from 14 pediatric centers, 150 had a PCD diagnosis verified. Median age was 15.05y, with range 0.15–60.5y. PCD prevalence was 1:54, 000 for the general population and 1:25, 000 in children (5-14 y). For the non-Jewish (mainly Druze and Arab Moslem) compared to Jewish populations, prevalence was 1:16, 500 and 1:139, 000 respectively (p < 0.0001) and parental consanguinity was 85.4% and 21.9% respectively (p < 0.0001). Clinical features included bronchiectasis (88%), rhinitis (81%), recurrent pneumonia (78%), recurrent otitis (62%), neonatal pneumonia (60%) and situs inversus (42%). Prior diagnostic practices varied widely between centers with TEM assessed in 55% and abnormal in 61% of these. Management included antibiotics and airway clearance. Diagnostic verification revealed for 150 PCD patients: 81% nNO<233 ppb, 62% abnormal HVMA, 51% diagnostic TEM, 58% diagnostic IF and, 57% genetic diagnosis. Conclusions: PCD in Israel is rare, with comprehensive diagnostic tests showing prevalence in children similar to Europe. Prevalence was higher in non-Jews, associated with parental consanguinity. Diagnostic and management practices vary. Referral centers providing comprehensive diagnostic and care capabilities should be established. Highlights: Prevalence of PCD in Israel was determined using a comprehensive battery of diagnostic tests. PCD prevalence was higher in the non-Jewish population than in the Jewish population in Israel. First detailed report on the demographics and clinical features for PCD in Israel.